Respuesta :

6sqrt3 = sqrt(36*3) = sqrt108 

so choice B is right sure 

hope helped 

Answer:

The equivalent expression will be  [tex]5i\sqrt{3}[/tex]

Step-by-step explanation:

The given expression is:   [tex]\sqrt{-108}-\sqrt{-3}[/tex]

[tex]\sqrt{-108}-\sqrt{-3}\\ \\ =\sqrt{36*(-3)}-\sqrt{-3}\\ \\ =\sqrt{36}*\sqrt{-3}-\sqrt{-3}\\ \\ =6\sqrt{-3}-\sqrt{-3}\\ \\ =5\sqrt{-3}\\ \\ =5i\sqrt{3}[/tex]

[As  [tex]i= \sqrt{-1}[/tex]]

So, the equivalent expression will be  [tex]5i\sqrt{3}[/tex]

ACCESS MORE